The tadpole of Rhinella abei (Baldissera, Caramaschi, and Haddad, 2004) - Fehlberg, Bruno Henrique Barbosa; Natali, Felipe; Pezzuti, Tiago Leite; de Anchietta Garcia, Paulo Christiano (Zootaxa, 2012)
The R. crucifer group is composed by five species: R. crucifer (Wied-Neuwied), R. ornata (Spix), R. henseli (A. Lutz), R. pombali and R. abei (Baldissera, Caramaschi & Haddad). In Brazil, these species are distributed in coastal areas, being found in ponds and streams inside forests or in open areas (Heyer et al. 1990; Baldissera et al. 2004). Rhinella abei was described by Baldissera, Caramaschi & Haddad in 2004 to allocate the populations of R. crucifer from east of Paraná, Santa Catarina and Rio Grande do Sul States. Herein, we describe R. abei tadpoles, collected in a swamp area, next to Praia dos Naufragados (27°49’51.78”S, 48°33’40.25”W; 11 m a. s. l.) Florianópolis, state of Santa Catarina Brazil, in the beginning of September 2010.